DINAMIKA KOMUNIKASI LINGKUNGAN DALAM MEMBENTUK MOTIVASI HAFALAN AL-QUR’AN PADA SANTRI DI PPTQ SABILUL MUTTAQIN PUNGGING MOJOKERTO - syafa'at, wahyu (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mmojokerto, 2024)
This study aims to uncover how the dynamics of environmental communication at the Tahfidzul Qur'an Islamic Boarding School Sabilul Muttaqin in Pungging, Mojokerto influence and shape the motivation of students in memorizing the Quran from an early age. This research employs a qualitative approach with in-depth interviews, observations, and document analysis to collect data from various relevant sources and informants. The research findings indicate that the Tahfidzul Qur'an Islamic Boarding School Sabilul Muttaqin creates a highly supportive environment for Quran memorization. Intensive communication among students, teachers, and fellow students provides a positive boost to students' learning motivation. The quality of warm and inclusive interpersonal interactions creates a conducive climate for religious learning, including Quran memorization. This article concludes that environmental communication at the Tahfidzul Qur'an Islamic Boarding School Sabilul Muttaqin plays a significant role in shaping students' motivation in Quran memorization. Therefore, a communicative approach in the boarding school environment can serve as a relevant model for enhancing students' motivation in understanding and memorizing the Quran.